Glial phagocytosis for synapse and toxic proteins in neurodegenerative diseases - Yeseong Choi; Won-Suk Chung (Molecular Neurodegeneration)
Abstract Glia, as resident immune and supportive cells of the central nervous system, play a critical role in maintaining brain homeostasis. One of their key homeostatic functions is phagocytic capacity in pruning synapses and removing cellular debris/protein aggregates, a process vital for synaptic plasticity and brain maintenance. However, these phagocytic functions are often dysregulated with aging and in neurodegenerative diseases (NDs), such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and frontotemporal dementia. This review aims to examine the phagocytic roles of glia under both physiological and pathological conditions, with a special focus on their interactions with misfolded protein aggregates, including amyloid beta, tau, alpha synuclein, prion, huntingtin, and TAR DNA-binding protein 43. We also explore the fate of ingested molecules after being phagocytosed by glia—whether they are degraded, accumulate intracellularly, or are transferred between cells—and their implications for disease progression. Finally, we review current therapeutic strategies and the potential approaches for modulating glial phagocytosis to mitigate several NDs. We believe that understanding the exact mechanisms of glial phagocytosis and clearance will serve as key elements in developing future treatments for NDs.